Influence of bone density, screw size and surgical procedure on orthodontic mini-implant placement – part B: implant stability. Issue 4 (April 2021) - Möhlhenrich, S.C.; Heussen, N.; Modabber, A.; Bock, A.; Hölzle, F.; Wilmes, B.; Danesh, G.; Szalma, J.
Abstract: This in vitro study aimed to investigate the influence of bone density, implant size, and surgical procedure on the primary stability (PS) of orthodontic mini-implants (OMIs). In total, 640 OMIs of various sizes (2.0 × 7, 2.3 × 7, 2.0 × 11 and 2.3 × 11 mm) were inserted in the artificial bone of different densities (D1–D4). Placement was performed with an insertion angle of 90° or 60° to the bone surface and in 320 cases without predrilling, which resulted in 64 groups. PS was measured on the basis of implant stability quotient (ISQ) and insertion torque (IT). With regard to all possible influencing parameters, the mean PS differed between 39.20 and 60.00 (ISQ), and 10.00 and 39.00 Ncm (IT). The effect of OMI size and surgical procedure was dependent on bone quality. For example, implant size had less effect in high-density bone and was stronger with decreasing density. Overall, implant length had a greater influence than the diameter, and a high correlation was found among both PS measurement techniques. Therefore, a suitable choice of implant size and surgical protocol with regard to bone density can positively influence PS. In principle, ISQ and IT are suitable for measuring OMI stability.